Characterising the fluctuation of microRNA expression throughout a full menstrual cycle. (December 2015) - Bexon, Kimberley; Williams, Graham
Abstract: When processing a crime scene, obtaining a DNA profile that can identify an individual is extremely important. However, the identification of the body fluid that the sample was obtained from could provide key information of the events that occurred. microRNA (miRNA) expression analysis is a technique that has the potential to differentiate body fluids. The presence and expression of body fluid specific miRNA would provide a fast and effective tool for progressing crime scene investigation, especially alleged sexual assault cases. Forensic case work lacks methods for identifying vaginal material, venous blood, menstrual blood and azoospermatozoic seminal fluid within samples. A large screening study followed by a 31 day study on five female volunteers was performed utilising RT-qPCR on a large panel of body fluid markers. Screening showed a selection of markers were suitable to differentiate each body fluid, in some cases however, expression fluctuated when analysed over a 31 day period. The data shows that hsa-miR-412 may be suitable for identifying menstrual blood, expression from markers hsa-miR-124 and hsa-miR-205 varied significantly over the 31 day period and between individuals and therefore were less suitable for body fluid identification. The data supports the use of miRNA markers for the identification of certain body fluids such as menstrual and venous blood; however markers for the identification of body fluids such as vaginal material and saliva require further investigation.